Genome organization changes in GM and non-GM soybean [Glycine max (L.) Merr.] under salinity stress by retro-transposition events - Gözükırmızı, Nermin; Arı, Şule; Şahin, Olcay; Karlık, Elif; MERİÇ, SİNAN (My University, 2020)
Genetically modified (GM) crops are developed and cultivated worldwide, providing protection against insects and diseases, or tolerance to herbicides. However, despite the advantages that GM crops, they pose many concerns not only to human and animal health but also to the environment. In the present study, we perform inter-retrotransposon amplified polymorphism (IRAP)-PCR to reveal SIRE1, Bagy2 and Nikita transposition events in soybean [Glycine max (L.) Merr.] and GM soybean under increasing salt stress conditions (0 mM as control, 80 mm, 120 mM, 160 mM and 200 mM NaCl). Salinity dramatically affected soybean and GM soybean in a similar way that stem lengths, root lengths and leaf areas were reduced compared to control. According to IRAP-PCR results, polymorphism ratios of SIRE1, Bagy2 and Nikita retrotransposons among all samples were found to be 22–100%, 0–73% and 37–100%, respectively. These results are the first direct report to demonstrate the relationship between TEs polymorphisms and salinity stress in soybean and GM soybean. TEs, which may explain part of the new phenotypes, play essential roles in genome and gene evolution. Such information can be useful to understanding of genome organization differences derived from TEs between soybean and GM soybean.